Inclusive leadership and innovative work behavior: exploring the impact of employee voice as a mediating factor - Aslan, Hüseyin; Aksoy, Alptuğ; Yalpa, Bilgen Gaye (Arts and Science Press Pte. Ltd., 2024)
The main purpose of this field study is to examine the mediating role of employee voice in the effect of inclusive leadership perceptions on innovative work behaviors of employees working at different hierarchical levels in the manufacturing sectors. 415 employees in total were voluntarily included in the survey study. The findings obtained in this direction revealed that employees' perceptions of inclusive leadership positively affect their innovative work behavior attitudes and that employee voice has a mediating role in the relationship between these two variables. In this context, the sectoral results of the research are discussed, the limitations of the study are stated and certain suggestions are made for the employees working in managerial positions. © 2024 by author(s).
Keywords: employee voice; inclusive leadership; innovative work behavior